BSCI-06 COMPREHENSIVE ANALYSIS OF THE IMMUNOGENOMICS OF TRIPLE NEGATIVE BREAST CANCER BRAIN METASTASES FROM LCCC1419. (5th August 2022) - Van Swearingen, Amanda; Routh, Eric; Sambade, Maria; Vensko, Steven; McClure, Marni; Woodcock, Mark; Chai, Shengjie; Cuaboy, Luz; Wheless, Amy; Garrett, Amy; Carey, Lisa; Hoyle, Alan; et al.
Abstract: BACKGROUND: Triple negative breast cancer (TNBC) lacks expression of hormone receptors (estrogen and progesterone receptors, ER and PR) and HER2. Almost 50% of patients with metastatic TNBC will develop brain metastases (BrM), often with concurrent progressive extracranial disease. While immunotherapy has shown promise in the treatment of advanced TNBC, the immune profile of BrM remains largely unknown. To inform the development of immunotherapy strategies in this aggressive disease, we characterized the genomic and immune landscape of TNBC BrM and matched primary tumors. METHODS: Formalin-fixed, paraffin-embedded samples of BrM and primary tumors of patients with clinical TNBC (n=25, n=9 matched pairs) from the LCCC1419 biobank at UNC-Chapel Hill were analyzed by whole exome (WES) and RNA sequencing, with matched blood DNA sequenced for identification of somatic variants. Mutational and copy number alteration analyses, neoantigen prediction, and transcriptomic analysis of the tumor immune microenvironment were performed. RESULTS: Primary and BrM tissues were confirmed as TNBC and of the basal intrinsic subtype. Compared to primary tumors, BrM demonstrated higher tumor mutational burden. Neoantigen prediction showed elevated cancer testis antigen- and endogenous retrovirus-derived MHC class I-binding peptides in both primary tumors and BrM, and predicted single nucleotide variants (SNV)-derived peptides were significantly higher in BrM. BrM demonstrated reduced immune gene signature expression, although a signature associated with fibroblast-associated wound healing was elevated in BrM. Metrics of T and B cell receptor diversity were also reduced in BrM. CONCLUSIONS: BrM harbored higher mutational burden and SNV-derived neoantigen expression along with reduced immune gene signature expression relative to primary TNBC. Further research will expand these findings to other breast cancer subtypes. Exploration of immunomodulatory approaches including vaccine applications and immune checkpoint inhibition to enhance anti-tumor immunity in TNBC BrM are warranted.